Neuro-ophthalmological aspects of idiopathic intracranial hypertension (Ukrainian Journal of Ophthalmology, 2026)
Neuro-ophthalmological aspects of idiopathic intracranial hypertension
Keywords: idiopathic intracranial hypertension; papilledema; secondary optic atrophy